2016
DOI: 10.4236/ampc.2016.67019
|View full text |Cite
|
Sign up to set email alerts
|

Examples of Non-Uniqueness of the Equilibrium States for a Floating Ball

Abstract: We provide a numerical algorithm for numerically approximating a centrally located floating ball. We give examples of equilibria, and we present non-unique cases for the same physical parameters when the density of the ball is either greater than the supporting liquid (heavy) or lighter than the density of the vapor above (light). We classify the non-uniqueness by analyzing a function related to the force balance. We derive the potential energy of these states, and make comparisons of the non-unique cases. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We also showed in [MT13] that at least two equilibria can be expected, one a local minimum for energy and another a local maximum among a one parameter family of pseudo-equilibria, which will be defined below. Numerical calculations described in [Tre16] also suggested that this situation prevails with some generality as the physical parameters are varied.…”
Section: Introductionmentioning
confidence: 88%
“…We also showed in [MT13] that at least two equilibria can be expected, one a local minimum for energy and another a local maximum among a one parameter family of pseudo-equilibria, which will be defined below. Numerical calculations described in [Tre16] also suggested that this situation prevails with some generality as the physical parameters are varied.…”
Section: Introductionmentioning
confidence: 88%